Comparative Efficacies of Linezolid vs. Tedizolid in an Experimental Murine Model of Vancomycin-Resistant Enterococcal (VRE) Bacteremia - Abdelhady, Wessam; Mishra, Nagendra N. (Frontiers in Medicine, 2019)
Tedizolid (TZD) is an oxazolidinone derivative which demonstrates bacteriostatic activity through inhibition of protein synthesis. We compared the efficacies of TZD and an earlier-generation oxazolidinone, linezolid (LZD), in an experimental murine model of bacteremia caused by two VRE strains (one each E. faecium and E. faecalis). LZD exhibited significantly better efficacy in terms of reduced VRE blood and target tissue densities than TZD in this model.